Відповідь: х₁=0 , х₂=4,3 , х₃= 0,5
Покрокове пояснення:
( якщо хоч один множник буде рівний 0, то і весь вираз буде рівний 0)
-7x(2x-8,6)(1,5-3x)=0
-7х=0 або 2х-8,6=0 або 1,5-3х=0
х₁=0 або 2х=8,6 або -3х=-1,5 х=8,6:2 або х=-1,5:(-3)
х₂=4,3 або х₃= 0,5
Ответ:
фото
Пошаговое объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь: х₁=0 , х₂=4,3 , х₃= 0,5
Покрокове пояснення:
( якщо хоч один множник буде рівний 0, то і весь вираз буде рівний 0)
-7x(2x-8,6)(1,5-3x)=0
-7х=0 або 2х-8,6=0 або 1,5-3х=0
х₁=0 або 2х=8,6 або -3х=-1,5
х=8,6:2 або х=-1,5:(-3)
х₂=4,3 або х₃= 0,5
Verified answer
Ответ:
фото
Пошаговое объяснение: